Contribution to the treatment of nausea and emesis induced by chemotherapy in children and adolescents with osteosarcoma - Luisi, Flavio Augusto Vercillo; Petrilli, Antônio Sérgio; Tanaka, Cristiana; Caran, Eliana Maria Monteiro (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Chemotherapy-in- duced emesis is a limiting factor in treating chil- dren with malignancies. Intensive chemotherapy regimens along with emetogenic drug administra- tion have increased the frequency and severity of emesis and nausea. Our study was designed to consider the importance of this problem and the need for improvement in emesis treatment for patients receiving chemotherapy. Our objective was to compare the efficacy and safety of the antiemetic drug granisetron and a regimen of metoclopramide plus dimenhydrinate. DESIGN AND SETTING: Open, prospective and randomized study at Instituto de Oncologia Pediátrica, Department of Pediatrics, Universi- dade Federal de São Paulo. METHODS: From February to August 1994, 26 patients (mean age: 14 years) with osteo- sarcoma received 80 chemotherapy cycles of iphosphamide (2,500 mg/m2) plus epirubicin (75 mg/m2) or carboplatin (600 mg/m2), or epirubicin (75 mg/m2) plus carboplatin (600 mg/m2). Eighty chemotherapy treatments were analyzed regarding nausea and vomiting control. Patients were randomized to receive either a single dose of granisetron (50 µg/kg) or metoclopramide (2 mg/kg) plus dimenhydrinate (5 mg/kg infused over eight hours). Emesis and nausea were monitored for 24 hours by means of the modified Morrow Assessment of Nausea and Emesis. Statistical analysis utilized the chi- squared, Student t and Mann-Whitney tests, plus data exploration techniques. RESULTS: 62.5% of the patients undergoing che- motherapy responded completely to granisetron, whereas 10% responded to metoclopramide plus dimenhydrinate (p < 0.0001). No severe adverse reactions were found in either of the treatments given. CONCLUSION: In children and adolescents with osteosarcoma, granisetron was safe and more efficient than metoclopramide plus dimenhydri- nate for controlling chemotherapy-induced emesis and nausea.